Alpha synuclein overexpression can drive microbiome dysbiosis in mice - Timothy R. Sampson; Zachary D Wallen; Woong-Jai Won; David G. Standaert; Haydeh Payami; Ashley S. Harms (Scientific Reports)
Abstract Growing evidence indicates that persons with Parkinson disease (PD), have a unique composition of indigenous gut microbes. Given the long prodromal or pre-diagnosed period, longitudinal studies of the human and rodent gut microbiome before symptomatic onset and for the duration of the disease are currently lacking. PD is partially characterized by the accumulation of the protein α-synuclein (α-syn) into insoluble aggregates, in both the central and enteric nervous systems. As such, several experimental rodent and non-human primate models of α-syn overexpression recapitulate some of the hallmark pathophysiologies of PD. These animal models provide an opportunity to assess how the gut microbiome changes with age under disease-relevant conditions. Here, we used a transgenic mouse strain, which overexpress wild-type human α-syn to test how the gut microbiome composition responds in this model of PD pathology during aging. Using shotgun metagenomics, we find significant, age and genotype-dependent bacterial taxa whose abundance becomes altered with age. We reveal that α-syn overexpression can drive alterations to the gut microbiome composition and suggest that it limits diversity through age. Taxa that were most affected by genotype-age interaction were Lactobacillus and Bifidobacteria. In a mouse model, we showed direct link between alpha synuclein geneotype (hallmark of PD), a dysbiotic and low-diversity gut microbiome, and dysbiotic levels of Bifidobacteria and Lactobacillus (most robust features of PD microbiome). Given emerging data on the potential contributions of the gut microbiome to PD pathologies, our data provide an experimental foundation to understand how the PD-associated microbiome may arise as a trigger or co-pathology to disease.